(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The study was conducted from 1/10/2023 to 1/5/2024 on strawberry Camarosa cv seedlings . planted in one of the plastic houses belonging to Horticulture and Landscape Design Dep. / Agriculture and Forestry college / mosul University aim of determining the effect of adding Bio fertilizers, namely Azotobacter, which were added at three levels (0, 2 and 4 g plant-1), and Azospirillum at three levels as well (0, 2and 4 g plant-1), and two levels of mycorrhizal fungi (0 and5 g plant-1). All fertilizers from bacteria and fungi were added at once and distributed randomly. The experment was executed a Randomized Complete Block Design (RCBD) with three replications and 8 plants per experimental unit. The results were statistically analyzed according to the design used, and the means were compared using Duncan’s multiple range test at a probability level of 0.05. The results confirmed that adding Azotobacter, Azospirillum at levels of 4 g plant -1 for each, and mycorrhizal fungi at level of 5g plant-1 individually, as well as their triple interaction, significantly increased available concentration of nitrogen, phosphorus, and potassium in the soil ,meanwile soil pH unsignificantly effected with the application of bio-fertilizers.